Development and Field Application of a New Ultralow Guar Gum Concentration Weighted Fracturing Fluid in HPHT Reservoirs - Yi Liu; Jing Liu; Yunzi Li; Hui Yang; Fei Yan; Jiapeng Zheng; Jun Wu; Jianyi Huang; Zuohao Wu; Cheng Luo; Junkai Lu (Journal of Chemistry)
A weighted fracturing fluid with superlow guar gum concentration was developed by synthesizing a polyboric acid cross-linker. The density of this fluid is 1.365 g/cm3 and can withstand very high temperature up to 175°C. In this study, a weighting agent was selected, and crosslinking ligands and boric acid were optimized. The crosslinking performance, base fluid viscosity, rheology, and gel-breaking performance of this fracturing fluid were studied. Compared with the conventional weighted fracturing fluid, the concentration of guar gum in the new weighted fracturing fluid can be reduced by 30% at the same temperature condition; moreover, crosslinking can be delayed by 2 minutes. The concentration of gel breaker used in this fluid can be significantly reduced to 0.005%∼0.01%. Two field tests were conducted in Jidong oil field, and both of them achieved great success.